THE LEGAL PROTECTION OF INNOVATIVE TECHNOLOGIES IN THE TRANSPLANTATION OF VITAL ORGANS. WAYS OF INTRODUCTION OF INVENTIONS: PROBLEMS AND PROSPECTS - M. V. Nikitina; O. P. Shevchenko (Вестник трансплантологии и искусственных органов)
The article deals with the legal protection of inventions in V.I. Shumakov Federal Research Center of Transplantology and Artifi cial Organs